Analisis Isu Islamophobia Di Jerman: Studi Kasus Muhammadiyah Sebagai Organisasi Gerakan Islam Modernis Indonesia - Agustari, Agustari (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
The case of Islamophobia is one of the cases that is often reported in the German media, which is closely related to the failure of multiculturalism politics which has an impact on the emergence of a negative stigma against Islam. Being a Western country with the largest Muslim population in Europe with a total of approximately 5.3 to 5.6 million people, based on data from the Federal Office for Migration and Refugees (BAMF) in 2021, the German government's policy towards Muslim immigrants is very exclusive and limited. Despite the many negative stigmas, Islam has been transformed into one of the major entities whose existence is considered. Muhammadiyah is one of the Islamic organizations in Indonesia that has diasporaized the